(untitled) - Seth, Vikram (London, 1993)
Opening and closing with a wedding, this novel is ostensibly the story of a Hindu family trying to find a suitable husband for their younger daughter, Lata. Who will the suitable boy turn out to be? The dashing Kabir, with whom Lata falls in love? The ambitious businessman whom Lata's mother favors? Or the sophisticated poet her relatives choose? The interwoven stories of four families linked by marriage form the background for this marital quest. It proves slow-moving at first, but the patient reader will inevitably be caught up in the compelling rhythms of a richly complex tale. The setting--India in the 1950s--is vividly realized: the enormity of the subcontinent, its overpowering heat, lush gardens, colorful festivals, and exotic foods. Memorable characters abound; not since Dickens has there been such a lively and idiosyncratic cast crowded into one novel. Drama is provided by the simmering conflict between Hindu and Muslim, which breaks out unexpectedly throughout the novel
Keywords: India,Ấn Độ; Fiction,Tiểu thuyết